Induction of Resistance to Fluconazole and Caspofungin in Candida glabrata Followed by Phenotypic and Genotypic Characterization - Chedraoui, Christy Antonios (2023)
Induction of Resistance to Fluconazole and Caspofungin in Candida glabrata: Phenotypic and Genotypic Characterization of Susceptible and Laboratory in-vitro Resistant Isolates by Christy Antonios Chedraoui is a study on the non-filamentous yeast, C. glabrata. Candida glabrata is an opportunistic, pathogenic fungus that is increasingly being isolated from hospitalized patients. The incidence of drug resistance is on the increase worldwide due to an overuse and misuse of antifungal drugs. The fungi’s virulence factors aids in its pathogenicity and ability to gain resistance. The aim of this study was to render an inherently sensitive C. glabrata strain resistant through sequentially increased exposure to two well-known and liberally-used antifungal drugs. These drugs are fluconazole, an azole that targets ergosterol biosynthesis, and caspofungin, an echinocandin that targets cell wall glucan synthesis. The resistant isolates were analyzed phenotypically for pathogenicity attributes such as ergosterol and chitin content, the ability to form biofilms, the strength of the cell wall, growth rates, adherence to agar, and virulence in a mouse model of disseminated candidiasis. Our results showed a change in the latter two characteristics, with a decrease in adhesion and an attenuation of virulence in isolates exposed to the drugs. Such a decrease in fitness is known to occur when resistance is gained. Additionally, an increase in the ability to form biofilms was also observed. Furthermore, whole genome sequencing of the resistant isolates was performed to determine mutations in key genes that might correlate with the observed phenotypes. The majority of mutations were found in genes implicated in adhesion, such as in the AWP, PWP, and EPA family of genes, which might explain the observed decrease in adhesion. Mutations were also found in genes that have not yet been fully characterized. Finally, isolates exposed to higher drug concentrations displayed more mutations than those at lower concentration. Our study is the first of its kind to induce drug resistance in C. glabrata followed by whole genome sequencing and phenotypic characterization.